Optimisation And Response Surface Methodology Study Of Lauric Acid And Palm Fatty Acid Distillate Into Methyl Esters By Catalytic Esterification - Nadarajah, Sivajothi (2020)
Biodiesel has received a great deal of attention worldwide attributed to its ability to ease the environmental air pollution by reducing the use of fossil fuel and evert the warmer climate greenhouse gas effect. This study investigates the esterification of free fatty acid using both homogeneous and heterogeneous acid catalysts under mild reaction conditions.